Market orientation for the hotel segment : the portuguese case - Raposo, Mário (2010)
In view of the importance of the hotel segment for the tourism and for the economy of countries such as Portugal, the objective of this study was to measure the level of orientation for the market of the largest hotel groups of Portugal. This investigation initially emphasized the importance of the marketing for the organizations, mainly the orientation for the market. After a brief explanation on the hotel segment in Portugal, an empirical study was presented, of quantitative, exploratory and traversal character, performed with the largest groups of 20 hotels of Portugal, using as an instrument of collection data, the traditional Markor scale (market orientation) adapted to the hotel sector. After analyzing the data, it was found in the investigated organizations that a good capacity to generate market information and response to the market, which formed two of the three constructs of Markor scale. However the results obtained with the construct of the dissemination of market information were below the expectations. It was possible to conclude that marketing professionals of the large hotel groups in Portugal are well oriented to the market, something not shared by other investigated departments of the hotels. So the current challenge for the main networks of hotels in Portugal is to improve the internal dissemination of information that marketing professionals gathered at the market.